2021
DOI: 10.1016/j.eclinm.2021.101169
|View full text |Cite
|
Sign up to set email alerts
|

Nafamostat in hospitalized patients with moderate to severe COVID-19 pneumonia: a randomised Phase II clinical trial

Abstract: Background Nafamostat, a serine protease inhibitor, has been used for the treatment of disseminated intravascular coagulation and pancreatitis. In vitro studies and clinical reports suggest its beneficial effect in the treatment of COVID-19 pneumonia. Methods This phase 2 open-label, randomised, multicentre, controlled trial evaluated nafamostat (4.8 mg/kg/day) plus standard-of-care (SOC) in hospitalised patients with COVID-19 pneumonia (i.e., those requiring nasal high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 22 publications
1
46
0
3
Order By: Relevance
“…However, the results are still pending (NCT04657497). A phase II clinical trial of NM was conducted in 104 hospitalized patients who suffered from COVID-19 pneumonia and required oxygen supplementation [189]. Overall, intravenous administration of NM (4.8 mg/kg/day for 10 days) failed to improve the time to clinical improvement and recovery compared with the SOC group [189].…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are still pending (NCT04657497). A phase II clinical trial of NM was conducted in 104 hospitalized patients who suffered from COVID-19 pneumonia and required oxygen supplementation [189]. Overall, intravenous administration of NM (4.8 mg/kg/day for 10 days) failed to improve the time to clinical improvement and recovery compared with the SOC group [189].…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
“…A phase II clinical trial of NM was conducted in 104 hospitalized patients who suffered from COVID-19 pneumonia and required oxygen supplementation [189]. Overall, intravenous administration of NM (4.8 mg/kg/day for 10 days) failed to improve the time to clinical improvement and recovery compared with the SOC group [189]. However, a subgroup analysis of patients with worsened baseline clinical status revealed more rapid clinical improvement and a higher recovery rate in the study population treated with NM [189].…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
“…Recently, a phase 2 open-label RCT in patients requiring nasal high-flow oxygen therapy and/or non-invasive mechanical ventilation with COVID-19 showed NM did not shorten the time to clinical improvement [ 9 ]. The result of the study supports our findings but further validation may be needed by larger RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent previous basic experimental [ 5 ] and case reports or series [ 2 , 6 , 7 , 8 ] have suggested the potential effectiveness of NM against COVID-19. However, to our knowledge, neither clinical trials nor observational studies, except for a recent small phase 2 open-label, randomized controlled trial (RCT) [ 9 ] have demonstrated an association between NM and reduced mortality. Therefore, we aimed to evaluate the effect of NM in patients with COVID-19 using a large-scale in-patient database in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though TMPRSS2 and lysosomal cathepsins have been both demonstrated to have cumulative effects with furin on activating SARS-CoV-2 entry, inhibition of TMPRSS2 was found to be sufficient to prevent SARS-CoV-2 entry in lung cell lines and primary lung cells (148), raising hopes for their future use as antivirals in vivo. Accordingly, promising preclinical results obtained with Nafamostat, another TMPRSS2 inhibitor (149,150), are currently awaiting clinical confirmation (151).…”
Section: Could Inhibitors Of Cellular Proteases Be Used As Antivirals?mentioning
confidence: 99%